Pembelajaran Mahāratul kalām Berbasis Lingkungan Pondok Pesantren - Kamil, Abdul; Febriansyah, Hari; Purwasandy, Tubaagus Kesa (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
This study aims to explore and analyse the ability to speak (mahāratul kalām ) while learning Arabic in an Islamic boarding school environment. With a qualitative approach, this research involves students as the main subject in certain Islamic boarding schools, where data is collected through observation, interviews, and documentation. The results of the study show that the physical, social, and cultural environment of Islamic boarding schools strongly supports the Arabic language learning process by creating a conducive atmosphere for students to practicece speaking. Environment-based learning strategies, such as group discussions and daily dialogues, have proven to be effective in improving students' speaking skills. Despite the obstacles, such as lack of resources and the awkwardness of students, the proposed solution includes training for teachers and creating a more inclusive atmosphere. This research is expected to contribute to the development of Arabic language learning methods in Islamic boarding schools and increase the effectiveness of Arabic language mastery among students in.